Aspek Pertumbuhan Ikan Julung-Julung (Hemiramphus lutkei, Valenciennes 1847) yang Dipasarkan di Kabupaten Manokwari - Kelkusa, Kaimudin; Mudjirahayu, Mudjirahayu; Handayani, Tutik; Simatauw, Fanny F.C.; Saleh, Fitriyah Irmawati (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
This study aims to determine the biological aspects of julung fish by providing basic information regarding size distribution, sex ratio, length-to-weight relationship, growth pattern, and condition faktors. Data collection was carried out at Sanggeng Market and Borobudur market which are fish marketing places in Manokwari Regency, November 2021-January 2022 using a descriptive research method. Fish sampling was done randomly. The results showed that the sex ratio of male fish (1278 fish) was greater than the number of female fish (575 fish), this means that it was significantly different and did not follow a 1:1 ratio. The size distribution of julung-julung fish varies from 200-287 mm for male fish and 220-309 mm for females. Body weight 23-63 grams for males and 31-73 grams for females. The relationship between fish length and weight follows the regression equation W = 0.0021L1.779 for males, and W = 0.0235L1.3656 for females. The growth pattern of fish was allometric negative (b < 3) for both males and females. Condition faktor values ranged from 0.012-1.079 for males and 0.645-1.630 for females. The conclusion of this study is that fish growth is strongly influenced by faktors such as gender, age.